The Impact of a Modality Switch During Isokinetic Leg Extensions on Performance Fatigability and Neuromuscular Patterns of Response - John Paul V. Anders; Tyler J. Neltner; Robert W. Smith; Jocelyn E. Arnett; Richard J. Schmidt; Terry J. Housh (Sensors)
Bilateral (BL) and unilateral (UL) muscle actions are commonly incorporated in training programs to achieve distinct goals, however, the mechanisms driving modality-specific training adaptations remain unclear. This study examined peak force, electromyographic (EMG) amplitude (AMP), and mean power frequency (MPF) of the non-dominant leg during isokinetic leg extensions performed as either a BL or BLUL combined modality. Twelve recreationally trained men (Mean ± SD; age = 20.8 ± 1.7 years; weight = 83.1 ± 15.7 kg; height = 178.2 ± 7.8 cm) attended 2 test visits that included BL and UL maximal isokinetic leg extensions at 180°·s−1 followed by a fatiguing task of either 50 BL or 25 BL followed immediately by 25 UL (BLUL) maximal, isokinetic leg extensions at 180°·s−1, in random order on separate days. The results demonstrated a 33.3% decline in peak force with a concomitant increase in EMG AMP across the fatiguing task, but there were no significant differences between conditions. For EMG MPF, the BLUL condition exhibited a 19.39% decline versus a 10.97% decline in the BL condition. Overall, the present study suggested there were no significant differences in neuromuscular activation strategies between the tested modalities. However, our findings indicated that incorporating UL muscle actions after a BL task may induce a greater degree of peripheral fatigue compared to sustained BL muscle actions. Practitioners might consider implementing UL exercises at the end of a training bout to induce greater metabolic stress.